Restrição à participação auditiva: associação com as fragilidades física, cognitiva e social em pessoas idosas - Campos, Ruana Danieli da Silva Campos (2023)
The social, functional and structural changes in the individual as he ages generate socioeconomic and public health impacts. Elderly people demand specialized care and actions to prevent negative outcomes related to aging, such as frailty. Given the complexity of the multidimensional processes of fragility and its negative impacts, it is important to verify the aspects related to it. Hearing loss, as a prevalent condition in the elderly population with consequent emotional and social harm, such as restriction to participation, should be considered in studies with elderly populations. Thus, this dissertation aimed to verify whether there is an association between auditory participation restriction and frailty in elderly people. For this, a cross-sectional study was carried out with 238 elderly people (age ≥ 60 years), which resulted in two articles. Article 1: “Hearing Handicap and Frailty in Community Elderly People” whose objective was to verify the relationship between auditory handicap and frailty in community-dwelling elderly people. The Hearing Handicap Inventory for the Elderly - Screening version - HHIE-S questionnaire was applied to assess participation restriction through auditory handicap. Frailty was assessed according to the Frailty Phenotype proposed by Fried et al. As a result, there was a greater restriction on participation in pre-frail and frail individuals, compared to non-frail individuals. Article 2: “Restriction to participation and self-perception of hearing loss: association with physical, cognitive and social frailty in elderly people”. It aimed to verify the association between physical, cognitive and social frailty with the restriction of auditory participation in elderly people. Physical frailty was assessed according to the five criteria of the Phenotype of Frailty, cognitive frailty was characterized by the simultaneous presence of physical frailty and cognitive decline, as indicated by the Mini Mental State Examination (MMSE), and social frailty was assessed by an index of five questions from social domains. The Hearing Handicap Inventory for the Elderly - Screening version - HHIE-S questionnaire was applied to quantify the restriction to auditory participation. The results showed that the restriction on auditory participation was greater in groups with physical, cognitive and social frailty. Using the univariate logistic regression model with the calculation of odds ratio, it was found that at each point indicative of restriction to auditory participation, there was a 1.05 times increase in the chance of the individual belonging to the physical frailty group and 1.033 belonging to the group of cognitive fragility. There was no association between restriction of auditory participation and cognitive frailty. Thus, this dissertation showed that the restriction on auditory participation is related to physical, cognitive and social weaknesses, however, the associations were verified only between the restriction on participation and physical and cognitive weaknesses.